Agistemus aimogastaensis sp. n. (Acari, Actinedida, Stigmaeidae), a recently discovered predator of eriophyid mites Aceria oleae and Oxycenus maxwelli, in olive orchards in Argentina - Leiva, Sergio Dante (2013)
A new species, Agistemus aimogastaensis, is described with the aid of optical and Scanning Electron Microscopy. This mite is an important predator of two eriophyid mites (Aceria oleae and Oxycenus maxwelli) in olive orchards (Olea europaea, variety Arauco) in La Rioja Province. The problems related to eriophyids in olive orchards in Argentina are highlighted and photos of the damage on leaves and fruit are included.